«Mala domna» i «Dona de mal»: el rebuig de l'estimada infidel per part dels trobadors i dels poetes catalans de l'edat mitjana - de Riquer, Isabel (Caplletra. Revista Internacional de Filologia, 2005)
The Occitan «mala cansó» of the twelfth and thirteenth centuries and the Catalan «maldit» of the fourteenth and fifteenth centuries both display a singular aspect of medieval literary misogyny. In both cases criticism is not levelled against women in general, but against a particular lady who has been previously loved by the poet and is now rejected. The poet blames her directly and harshly because, after leaving him, she has given herself to a man from an inferior social background. As a result, the poet bids farewell to her and moves away. Some of the Catalan poets of the Middle Ages persisted in this literary outlet. They borrowed for their own «maldits» the motifs andexpressions that were characteristic of the break-up and the violent farewell, and adapted them to their own language and to the bourgeois environment of the towns.